Is bank debt special for the transmission of monetary policy? Evidence from the stock market - Filippo Ippolito; Ali K. Ozdagli; Ander Perez (Federal Reserve Bank of Boston, 2013)
We combine existing balance sheet and stock market data with two new datasets to study whether, how much, and why bank lending to firms matters for the transmission of monetary policy. The first new dataset enables us to quantify the bank dependence of firms precisely, as the ratio of bank debt to total assets. We show that a two standard deviation increase in the bank dependence of a firm makes its stock price about 25 percent more responsive to monetary policy shocks. We explore the channels through which this effect occurs, and find that the stock prices of bank-dependent firms that borrow from financially weaker banks display a stronger sensitivity to monetary policy shocks. This finding is consistent with the bank lending channel, a theory that posits that the strength of bank balance sheets matters for monetary policy transmission. We construct a new database of hedging activities and show that the stock prices of bank-dependent firms that hedge against interest rate risk display a lower sensitivity to monetary policy shocks. This finding is consistent with an interest rate pass-through channel that operates via the direct transmission of policy rates to lending rates associated with the widespread use of floating rates in bank loans and credit line agreements.
Keywords: G21; G32; E52; 330; bank lending channel; monetary policy transmission; firm financial constraints; bank financial health